Perancangan Taman Terapi Hortikultura Bagi Penderita Gangguan Jiwa Pada Rumah Sakit Jiwa Provinsi Bali - PUTRI, MAYA NORMA; ASTAWA, NYOMAN GEDE; UTAMI, NI WAYAN FEBRIANA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2013)
ABSTRACT Horticultural Healing Garden Design for People with Mental Disorder at Mental Hospital, Bali Province Mental Hospital of Bali Province is therapeutic referral place for people with mental disorders (stress to depression) which is using medical approach. The patient is largely a modern society that wasn’t able to cope with the pressures of life as its cause. The effect decreased by horticultural healing garden which aims to accommodate patient therapy with emotion and psychology approaches. Landscape designimg concept used Marcus and Barnes (1999) design principles for healing garden. This horticultural healing garden designing presents 1) variety spaces, 2) plant elements dominate garden, 3) support walking activity, 4) provide a positive diversion, 5) has natural lighting and sound, and 6) has clear and simple design. Keywords: landscape designing, horticultural therapy, healing garden, mental disorders, mental hospital designing
Keywords: landscape designing; horticultural therapy; healing garden; mental disorders; mental hospital designing